Viroporins vs. Other Pore-Forming Proteins: What Lessons Can We Take? - Eva Žerovnik (Frontiers in Chemistry, 2021)
Pore-forming proteins (PFPs) exist in virtually all domains of life, and by disrupting cellular membranes, depending on the pore size, they cause ion dis-balance, small substances, or even protein efflux/influx, influencing cell’s signaling routes and fate. Such pore-forming proteins exist from bacteria to viruses and also shape host defense systems, including innate immunity. There is strong evidence that amyloid toxicity is also caused by prefibrillar oligomers making “amyloid pores” into cellular membranes. For most of the PFPs, a 2-step mechanism of protein-membrane interaction takes place on the “lipid rafts,” membrane microdomains rich in gangliosides and cholesterol. In this mini-review paper, common traits of different PFPs are looked at. Possible ways for therapy of channelopathies and/or modulating immunity relevant to the new threat of SARS-CoV-2 infections could be learnt from such comparisons.